2016
DOI: 10.5606/kbbihtisas.2016.97059
|View full text |Cite
|
Sign up to set email alerts
|

Variable prevalence of allergic rhinitis and risk factors affecting the prevalence

Abstract: ÖZAlerjik rinit burunda akıntı, hapşırık, kaşıntı ve tıkanıklık, sıklıkla konjonktival enjeksiyon ve gözde kaşınmayla karakterize olan burun mukozasının kronik enflamasyonu olarak tanımlanmaktadır. Çocukluk çağı alerjik rinit prevalansı dünya çapında hızlı bir artış göstermektedir. Ancak bölgeler arasında bariz farklar vardır, bu da alerjik rinitin gelişiminde değişen genetik ve çevresel etkenlere işaret etmektedir. Bölgesel bu fark, genetik yatkınlık yanında çevresel ve davranışsal faktörlerin hızlı değişimiy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 86 publications
(155 reference statements)
0
9
0
Order By: Relevance
“…The major cause of this is considered that in all areas of Anatolia the most common allergens are house dust (D. farinae) and pollen groups. 48–50 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The major cause of this is considered that in all areas of Anatolia the most common allergens are house dust (D. farinae) and pollen groups. 48–50 …”
Section: Discussionmentioning
confidence: 99%
“…45,46 However, Luo et al 47 found a positive correlation between pet ownership and AR despite most of the pet owners being in rural areas where the AR prevalence is established to be almost four times less. 48 We questioned the current ownership of pets which was found to be positively related to AR (p=0.001) in the chi-squared test and the regression test (p<0.025).…”
Section: Dovepressmentioning
confidence: 97%
See 2 more Smart Citations
“…A number of researchers investigated the relation of animal allergens and AR, however the results were conflicting. It was reported that early exposure to animals was protective for AR, this was a risk factor for AR, or did not affect AR development ( 104 , 114 - 117 ).…”
Section: Diagnosis Of Allergic Rhinitismentioning
confidence: 99%